2011
DOI: 10.1159/000329519
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Corticosteroid/Long-Acting β<sub>2</sub>-Agonist Combination Therapy for Asthma: Attitudes of Specialists in Europe

Abstract: Background: As new combinations of inhaled corticosteroids (ICSs) and long-acting β2-agonists (LABAs) become available for the treatment of asthma, it will be important to determine criteria against which they can be evaluated. The aim of this study was to assess which attributes of combination therapy physicians consider most important. Methods: Primary and secondary care asthma specialists (n = 32) were recruited for an expert Delphi process that was performed over three rounds to determine attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…A rapid onset of action is important to patients, who want to feel their combination therapy working quickly, while providing lasting therapeutic benefits [59]. This is confirmed by the results of a Delphi initiative, which showed that expert respiratory specialists considered the potency of the ICS and speed of onset of the LABA among the most important factors when prescribing an ICS/LABA combination therapy for asthma [60]. Taken together, these data suggest that the combination of the ICS FP, which has potent anti-inflammatory effects, and the LABA FF, which provides rapid bronchodilation, provides an additional treatment option for asthma that may be valued by both physicians and patients for therapeutic efficacy and patient compliance.…”
Section: The Contribution Of the Device And The Formulation To The Lementioning
confidence: 89%
“…A rapid onset of action is important to patients, who want to feel their combination therapy working quickly, while providing lasting therapeutic benefits [59]. This is confirmed by the results of a Delphi initiative, which showed that expert respiratory specialists considered the potency of the ICS and speed of onset of the LABA among the most important factors when prescribing an ICS/LABA combination therapy for asthma [60]. Taken together, these data suggest that the combination of the ICS FP, which has potent anti-inflammatory effects, and the LABA FF, which provides rapid bronchodilation, provides an additional treatment option for asthma that may be valued by both physicians and patients for therapeutic efficacy and patient compliance.…”
Section: The Contribution Of the Device And The Formulation To The Lementioning
confidence: 89%
“…The LABA, formoterol fumarate (formoterol), has rapid, dose-dependent bronchodilatory effects, with an onset of action of 1 to 3 minutes [23], similar to salbutamol and faster than that of salmeterol [24-27]. Extensive research into the safety and efficacy of these two molecules is widely documented in the literature [19-30], and suggests that the fluticasone/formoterol combination may provide clinicians with a new and efficacious treatment for the management of persistent asthma.…”
Section: Introductionmentioning
confidence: 99%
“…GPs and specialists from European countries were asked to complete Delphi questionnaires and to take sequential surveys. At the end of this survey, a panel of experts highlighted six main characteristics of ICS/LABA combination treatment: i) dosage flexibility (88% of attendees), ii) safety and long-term tolerability of ICS (81%), iii) safety and long-term tolerability of LABA (81%), iv) efficacy in asthma control (69%), v) anti-inflammatory power of ICS (69%), vi) rapid bronchodilator activity of LABA (68%) [ Table 1] [29].…”
Section: Goals Of Asthma Managementmentioning
confidence: 99%
“…Table 1 Expert panel agreement ⁎ on the characteristics of an effective ICS/LABA combination therapy. The results refer to the final round of a Delphi process [29].…”
Section: Fluticasone Propionate and Formoterolmentioning
confidence: 99%